2016
DOI: 10.1097/mat.0000000000000293
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Maintenance of VV ECMO for 104 Days with Native Lung Recovery in Acute Respiratory Failure

Abstract: Recently, extracorporeal membrane oxygenation (ECMO) support has been increasingly applied in acute respiratory failure. The ECMO brings some advantages for enhancing the capacity of lung regeneration. Thus, the timing of determining irreversibility of the injured lung could be delayed. In this study, we experienced a case of prolonged maintenance of veno-venous ECMO for 104 days that resulted in native lung recovery. In this case, the initial empirical treatment showed no response within 4 weeks with ECMO sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Several other authors have also reported prolonged V-V ECMO with native lung recovery [ [2] , [3] , [4] , [5] , [6] , [7] , [8] ]. Akkanti et al reported a case of a 30-year-old man with influenza A who was weaned off V-V ECMO after 193 days and was ambulatory at discharge from the hospital [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other authors have also reported prolonged V-V ECMO with native lung recovery [ [2] , [3] , [4] , [5] , [6] , [7] , [8] ]. Akkanti et al reported a case of a 30-year-old man with influenza A who was weaned off V-V ECMO after 193 days and was ambulatory at discharge from the hospital [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the 2016 Extracorporeal Life Support Organization (ELSO) registry report, the average duration of V-V ECMO in adults with acute respiratory failure is 10.5–13.5 days [ 1 ]. Some patients whose lung damage is not improved may require support of V-V ECMO for more than 2 weeks, and recently, there have been more reports of prolonged V-V ECMO [ [2] , [3] , [4] , [5] , [6] , [7] , [8] ]. However, we do not know how long it is feasible to wait for native lung recovery or lung transplant (LTx) with the use of ECMO.…”
Section: Introductionmentioning
confidence: 99%
“…The management of ECMO therapy in patients without a decannulation strategy is further complicated when the patient is awake and an active participant in their care. A case report by Moon et al presented a 53-year-old patient on venovenous ECMO for acute respiratory failure [30]. After 4 weeks of ECMO treatment, recovery of native lung function appeared unlikely, and a lung transplant was suggested to the patient.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…From 1993 to 2007, there were no survivors of the nine patients supported on ECMO for 52 days or more in the ELSO database [116]. More recently, there have been many cases reported of long-term respiratory ECMO in both children and adults with good outcomes, including lung transplant or late lung recovery after up to 265 days of ECMO [116][117][118][119][120][121]. These reports are remarkable as, historically, it has been thought that if native lung function was not improving or restored at 2-4 weeks of ECMO support, the chance of recovery was remote [119].…”
Section: Long-term Ecmomentioning
confidence: 99%